Sinkronisasi Hukum Pidana Islam dan Undang-Undang Terorisme dalam Menangani Kejahatan Terorisme di Indonesia - Maymoni Syahputra; Karli Karli (LPPM Iblam School of Law, 2025)
Terrorism is a serious crime that threatens national security and social stability in Indonesia. The government has implemented various legal approaches to counter terrorism, including the enforcement of Law No. 5 of 2018, which focuses on preventive and repressive measures. Meanwhile, Islamic criminal law categorizes terrorism as jarīmah ḥirābah, imposing severe punishments to maintain public order and deterrence. The need to harmonize Islamic law and national anti-terrorism legislation is crucial to achieving a more comprehensive legal framework. This research employs a qualitative method with a normative legal approach, analyzing regulations and the interpretation of legal norms in practice. Primary data consists of official documents such as laws and court rulings, while secondary data includes legal literature, academic journals, and previous studies. The findings indicate that Islamic criminal law and Law No. 5 of 2018 share the same objective in combating terrorism but differ in their legal mechanisms and sanctioning principles. The integration of ḥirābah principles into Indonesia’s legal system can strengthen the moral and ethical legitimacy of counterterrorism policies while ensuring compliance with human rights standards. Additionally, the study emphasizes the importance of balancing national security with legal certainty and justice. Future counterterrorism policies should incorporate Islamic law principles through strategic legal reform and an inclusive deradicalization.